Understanding Xinjiang from a Chinese Nationalist’s Perspective - Harryanto Aryodiguno (President University, 2021)
This paper focuses on the Xinjiang conflict with the central government as one of the conflicts that have sparked the world's attention, especially in western countries. Western media spend their most effort on discussing Vocational Education and Training Centers, political issues, religion, idealism, and human rights in Xinjiang. And then, under the presuppositions of Western-Centrism, the Western media accuses China of violating human rights. However, the Chinese government emphasizes that what happened in Xinjiang is the unrest that has been happening because of the group that wants to separate from China. This paper seeks to explain the real events in Xinjiang, including the problems faced by Xinjiang and the Chinese government, culture, politics, and the psychology behind the western media. Keywords: Western-Centralism, Xinjiang, Uyghur, Islam, Politic